1989
DOI: 10.1111/j.1440-1681.1989.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gabaergic System in Prolactin Analgesia

Abstract: 1. The role of the GABAergic system in the analgesic action of prolactin was investigated using a pharmacological approach. 2. THIP, a GABAmimetic, per se produced an analgesic effect and potentiated the analgesic effect of prolactin and morphine. 3. Bicuculline, in subconvulsive doses, per se did not alter the number of writhings, while it attenuated the analgesic effect of prolactin. 4. These results indicate a positive role for the GABAergic system in prolactin induced analgesia. 5. Since THIP resembles mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Nifedipine and Other dihydropyridine calcium channel blocking agents were known to potentiate the analgesic action of opioids (Hoffmeister and Tettenborn 1986;Kavaliers 1987;Contreras et al 1988, and other compounds (Ramaswamy et al 1986;Thirugnanasambantham et al 1988;AntkiewiczMichaluk et al 1991) in naive animals and to counteract the acute symptoms of opiate withdrawal in vivo (Bongianni et al 1986;Baeyens et al 1987;Caro et al 1988;Pellegrini-Giampietro et al 1988;Ramkumar and E1-Fakahany 1988;Antkiewicz-Michaluk et al 1990)and in vitro (Valeri et al t990), but our present results show that nifedipine also potentiates the analgesic effect of morphine in rats in which, due to chronic morphine administration, the analgesic effect of the drug disappeared, and that chronic co-administration of nifedipine with morphine prevents the development of physical abstinence. In addition, our findings indicate that the potentiation of analgesic action of morphine by nifedipine is mainly caused by the drug action on supraspinal pain centers, as hired±pine in the dose used does not influence the morphine effect in the tail-flick test, reflecting spinal pain mechanisms, but potentiates the analgesia measured in the hot-plate test, reflecting supraspinal pain mechanisms (Yaksh 1978a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine and Other dihydropyridine calcium channel blocking agents were known to potentiate the analgesic action of opioids (Hoffmeister and Tettenborn 1986;Kavaliers 1987;Contreras et al 1988, and other compounds (Ramaswamy et al 1986;Thirugnanasambantham et al 1988;AntkiewiczMichaluk et al 1991) in naive animals and to counteract the acute symptoms of opiate withdrawal in vivo (Bongianni et al 1986;Baeyens et al 1987;Caro et al 1988;Pellegrini-Giampietro et al 1988;Ramkumar and E1-Fakahany 1988;Antkiewicz-Michaluk et al 1990)and in vitro (Valeri et al t990), but our present results show that nifedipine also potentiates the analgesic effect of morphine in rats in which, due to chronic morphine administration, the analgesic effect of the drug disappeared, and that chronic co-administration of nifedipine with morphine prevents the development of physical abstinence. In addition, our findings indicate that the potentiation of analgesic action of morphine by nifedipine is mainly caused by the drug action on supraspinal pain centers, as hired±pine in the dose used does not influence the morphine effect in the tail-flick test, reflecting spinal pain mechanisms, but potentiates the analgesia measured in the hot-plate test, reflecting supraspinal pain mechanisms (Yaksh 1978a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Like morphine, the analgesic response of THIP and muscimol was potentiated by nifedipine and antagonized by calcium chloride, suggesting that THIP and muscimol might alter calcium ion movements across the plasma membrane to elicit analgesia. Clonidine and TRH which utilize pathways other than the opioid system did not involve calcium in their analgesic response (Ramaswamy et al 1986a).…”
Section: Discussionmentioning
confidence: 99%
“…Similarities include naloxone sensitivity, development of tolerance, presence of cross tolerance with morphine and alterations of calcium transport across membranes (Ramaswamy et al 1983(Ramaswamy et al , 1985(Ramaswamy et al , 1986. Recently it has been demonstrated that ATP dependent potassium channels also play an important role in morphine analgesia (Ocana et al 1990;Wild et al 1991).…”
Section: Introductionmentioning
confidence: 99%